2020
DOI: 10.5194/bg-2020-162
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A comparison of bacterial communities from OMZ sediments in the Arabian Sea and the Bay of Bengal reveals major differences in nitrogen turnover and carbon recycling potential

Abstract: Abstract. The Northern Indian Ocean hosts two Oxygen Minimum Zones (OMZ), one in the Arabian Sea and the other in the Bay of Bengal. High-throughput sequencing was used to understand the total bacterial diversity in, the surface sediment off Goa within the OMZ of the Arabian Sea, and from off Paradip within the OMZ of the Bay of Bengal. The dominant phyla identified included Firmicutes (33.08 %) and Proteobacteria (32.59 %) from the Arabian Sea, and Proteobacteria (52.65 %) and Planctomycetes (9.36 %) from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 75 publications
3
2
1
Order By: Relevance
“…Isolates from OMZ sediments common to all three sampling sites, that is, from off‐Goa, off‐Cochin, and off‐Mangalore regions belonged to genera Alteromonas , Salegentibacter , Gracilibacillus , and Bacillus sp. These genera are previously reported from OMZ region of Arabian Sea (Gomes et al., 2019; Lincy & Manohar, 2020; Paingankar et al., 2020) except Gracilibacillus sp., as per our knowledge, not reported in OMZ region of Arabian Sea. Alteromonas sp.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Isolates from OMZ sediments common to all three sampling sites, that is, from off‐Goa, off‐Cochin, and off‐Mangalore regions belonged to genera Alteromonas , Salegentibacter , Gracilibacillus , and Bacillus sp. These genera are previously reported from OMZ region of Arabian Sea (Gomes et al., 2019; Lincy & Manohar, 2020; Paingankar et al., 2020) except Gracilibacillus sp., as per our knowledge, not reported in OMZ region of Arabian Sea. Alteromonas sp.…”
Section: Discussionsupporting
confidence: 67%
“…Previous study on OMZ sediments carried out in deep benthic eastern AS‐OMZby using metagenomic approach has reported a Shannon diversity ( H ) index of 4.4 (Divya et al., 2011), and in South and East China Sea sediment samples, H index is 2.52 and 7.96, respectively (Dang et al., 2008; Zhu et al., 2013). Recent bacterial diversity sediment studies using pyrosequencing method by Lincy and Manohar (2020) has reported a H index of 4.37 and 6.97 for OMZs of Arabian Sea and Bay of Bengal, respectively, while In our study, H index was highest at off‐Cochin, that is, 2.46. Simpson diversity index ranges between 0 and 1, the greater the value, the greater the diversity; the highest diversity was seen in off‐Cochin (0.95), while lowest at off‐Goa (0.79), thus confirming that the microbial population at off‐Cochin is highly diverse.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…The results obtained in this study corroborate with earlier observations on active sulphur cycle in marine sediments. The presences of members from Planctomycetes group that are involved in anammox reaction in OMZ sediments are consistent with similar studies in Arabian Sea and Bay of Bengal [55]. The OMZ sediments were also replete with methanotrophs including significant representation from the NC10 phylum member methylomirabilis, indicating their strong role in methane oxidation coupled with nitrite reduction.…”
Section: Bacterial Composition and Functional Implicationssupporting
confidence: 88%